I'm in Seattle, where are you? : a memoir - Kazār, Murtaḍá (Amazon Crossing, 2021)
"As the US occupation of Iraq rages, novelist Mortada Gzar, a student at the University of Baghdad, has a chance encounter with Morise, an African American soldier. It's love at first sight, a threat to them both, and a moment of self-discovery. Challenged by society's rejection and Morise's return to the US, Mortada takes to the page to understand himself"--